Rheological, mechanical and durability performance of some North African commercial binary and ternary cements - Mokhtaria Benkaddour; Said Kenai; Walid Yahiaoui; Hamza Bensaci; Jamal Khatib (Case Studies in Construction Materials, 2023)
Mineral additions are used in most cement plants for ecological and economic reasons. The variation in the type and source of these mineral additions has a strong influence on the characteristics of cements, which makes it difficult for site engineers to predict the performance of self-compacting mortars and concretes based on these cements and choose the appropriate type for a particular application. This study aims at contributing to the characterization of two binary (limestone or pozzolan) and two ternary (limestone with pozzolan or limestone-slag) commercial cements in North Africa and their influence on the rheology and mechanical and durability performance of self-compacting mortars (SCM) at early age and long term. V-Funnel, the Marsh cone and a rheometer were used to measure the rheological properties. Also, the heat of hydration, total shrinkage, mechanical strength, capillary water absorption and resistance to acid (HCl and H2SO4) and sulfate (Na2SO4 and MgSO4) were evaluated. The results showed the need for the appropriate choice of cement according to the desired performance at the fresh and hardened state. The benefit of using ternary cement with improved workability, decrease in viscosity and yield stress, reduced sorptivity, and higher compressive strength at long term and better resistance to sulfate and acid attacks has been proven. It has been shown that CEM II/A (L+S) improves workability as it significantly decreases viscosity (60 %) and yield stress (76 %); reduces sorptivity (22 %), improves compressive strength at a long term (19 %) and enhances resistance to sulfuric acid (32 %). The CEM II/A (L+Z) reduces porosity (19 %) and increases resistance to sulfate attack by 25 % and 57 % under Na2SO4 and MgSO4 respectively). The best behavior towards HCl attack is that of CEM II/A-Z which presents the lowest values of total shrinkage and hydration heat.